Self-delivery nanomedicine to overcome drug resistance for synergistic chemotherapy. (29th March 2021) - Zheng, Rong-Rong; Zhao, Lin-Ping; Liu, Ling-Shan; Deng, Fu-An; Chen, Xia-Yun; Jiang, Xue-Yan; Wang, Chang; Yu, Xi-Yong; Cheng, Hong; Li, Shi-Ying
Abstract : α-TOS and DOX-based self-delivery nanomedicine (α-TD) is prepared with a high drug loading rate. α-TD could induce mitochondria depolarization, ROS accumulation and ATP reduction to overcome drug resistance for cancer synergistic chemotherapy. Abstract : Multidrug resistance (MDR) is one of the prime reasons for the failure of cancer chemotherapy, which continues to be a great challenge to be solved. In this work, α-tocopherol succinate (α-TOS) and doxorubicin (DOX)-based self-delivery nanomedicine (designated as α-TD) is prepared to combat drug resistance for cancer synergistic chemotherapy. Carrier-free α-TD possesses a fairly high drug loading rate and improves the cellular uptake via the endocytosis pathway. More importantly, the apoptotic inducer α-TOS could elevate the reactive oxygen species (ROS) generation, disrupt mitochondrial function and reduce adenosine 5′-triphosphate (ATP) production, which facilitate the intracellular drug retention while decreasing its efflux. As a result, α-TD achieves a considerable synergistic chemotherapeutic effect against drug resistant cancer cells. Moreover, it also exhibits a preferable inhibitory effect on tumor growth with a low system toxicity in vivo . This synergistic drug self-delivery strategy would open a new window for developing carrier-free nanomedicine for overcoming drug resistance in cancer therapy.